International Instructor Preparing Teachers for Multicultural Classrooms in the United States: Teaching Intercultural Communication Competence Online. (June 2014) - McCalman, Claudia L.
Abstract : Globalization and recent demographic changes in the United States contribute to an increasing number of nonnative speakers of English in our classrooms. Such multicultural classrooms present different dynamics and challenges. Most teachers don't receive training in college to work with students whose first language and culture are different from their own. Perceiving the need to be better prepared to meet the learning needs of their incoming student population, these teachers chose to pursue the English as a Second Language certification. This chapter explores teachers' perceptions and experiences while learning content of a prerequisite intercultural course. The author, an international instructor, closes the chapter with her own reflections about the context.